Metode Pembelajaran untuk Membiasakan Siswa Berakhlakul Karimah - Nurhayati, Nurhayati; Hidayat, Rahmad; Kusen, Kusen (JOEAI (Journal of Education and Instruction), 2021)
The purpose of this study was to analyze the use of habituation procedures by the teacher in describing the students of SDIT Khoiru Ummah Rejang Lebong in habituation of morality and to analyze the supporting and hindering aspects of education. This research is a descriptive qualitative research, teachers and principals are the subjects in this study, interviews, observations and documentation are used to obtain data, data analysis uses a descriptive qualitative approach. The results showed that the cultivation of morality in SDIT Khoiru Ummah students was by applying the pious character, namely the straight aqidah indicator (salimul aqidah): which included: (a). Believe in Allah and His Messenger, (b). Dare/Not afraid to be alone, (c). Not superstitious, (d). Dare to say the truth, Conclusion, based on the results of the study, it shows that there are two supporting aspects in the habituation of morality, namely school and family. The inhibiting aspects include internal and external aspects that occur in the school environment. Keywords: Akhlakul Karimah Learning Method, Early Childhood Students